A multi-locus approach to discern conservation units and adaptive potential of Pacific Black Ducks across Australia and surrounding islands. (3rd April 2021) - Brown, Joshua I.; Lavretsky, Philip; Joseph, Leo; Roshier, David; Guay, Patrick-Jean; Peters, Jeffrey L.
ABSTRACT: Genetic diversity, population delineation and rates of gene flow can be used to help understand long-term population dynamics, which is important for conserving species with fragmented distributions. Here, we sequenced 19 nuclear introns (nuDNA) and a portion of mitochondrial DNA (mtDNA) across three subspecies of Pacific Black Ducks ( Anas superciliosa ssp.; N mtDNA  = 162; N nuDNA  = 49) from Australia and surrounding islands in order to measure levels of genetic structure and gene flow. First, despite evidence of gene flow from Australia, Pacific Black Ducks from the Solomon Islands were significantly differentiated from all other groups in both mtDNA and nuDNA. This is probably due to genetic drift resulting in lowered genetic diversity. We found the lowest levels of genetic differentiation between locations sampled in Australia, suggesting strong connectivity across the continent. Despite elevated differentiation in mtDNA between Australia and other islands (i.e. Timor, New Zealand), low nuDNA divergence suggests some connectivity. Such marker discord is common among waterfowl and is likely due to male-biased dispersal from Australia. Finally, mtDNA of Pacific Black Ducks from New Zealand showed introgression of haplotypes from feral mallards ( A. platyrhynchos ), which were established in the 1800s. Overall, these data suggest that A. superciliosa ssp. consist of three distinct genetic units that correspond with subspecies classifications and require individual conservation planning.